Humanitarian and medical challenges of assisting new refugees in Lebanon and Iraq - Abu Sa’Da, C; Serafini, M (Refugee Studies Centre, University of Oxford, 2013)
The massive and continuing flows of Syrian and Palestinian refugees to Syria’s neighbours have shown the limitations of humanitarian practice and present new challenges for medical and humanitarian interventions